Manufacture of Industrial Scale Bagasse Biochar: Effect of Temperature And Residence Time And Biochar Characterization - Jaka Kuncara; Martomo Setyawan; Dhias Cahya Hakika (Equilibrium Journal of Chemical Engineering, 2025)
Abstract. Bagasse is a waste that can still be utilized, one of which is processed into biochar. In this study, bagasse waste came from a sugar factory in Majalengka, Cirebon, West Java. The bagasse pyrolysis process was carried out at PT XXX biochar factory located in the area. Industrial scale biochar production is done by Rotary Carbonization Furnace. The research objective was to characterize biochar with variable residence time and pyrolysis temperature. Biochar was characterized based on physicochemical properties and surface composition analysis for use as a soil improver and adsorbent. The test results show that residence time and pyrolysis temperature affect biochar products. Physical characterization showed that the pyrolysis residence time of 24.73 minutes with a temperature of 400 oC gave biochar results with pH (8.92), c-organic (24.15%), total N (0.2%), P2O5 (0.17%) and high C/N ratio (1,208.00). This biochar has good quality for application as a soil improver, especially in increasing carbon storage capacity and improving soil pH. The high C/N ratio and low nitrogen content require alloying with other sources to increase nitrogen and phosphorus and lower the C/N ratio. Chemical characterization by BET test showed that pyrolysis residence time of 24.73 min at 400 oC gave the best results in terms of increasing surface area (0.554 m²/g) and pore volume (0.00364 cc/g), making it the optimal temperature to produce biochar with high adsorption capacity. Surface characterization by SEM-EDX mapping analysis showed that the pyrolysis residence time of 24.73 min at 400 oC gave results with relatively high composition of carbon (82.17%), oxygen (14.89%), silica (1.97%), potassium (0.42%), and made it more effective for soil conditioner applications.Keywords: Bagasse, Biochar, Pyrolysis.